Ages of asteroid families estimated using the YORP-eye method. Issue 2 (31st December 2018) - Paolicchi, Paolo; Spoto, F; Knežević, Z; Milani, A
ABSTRACT: Recently, we have shown that it is possible, despite several biases and uncertainties, to find footprints of the Yarkovsky–O'Keefe–Radzievskii–Paddack (YORP) effect, concerning the members of asteroid dynamical families, in a plot of the proper semimajor axis versus magnitude (the so-called V-plot). In our previous work, we introduced the concept of the YORP-eye, the depopulated region in the V-plot, whose location can be used to diagnose the age of the family. In this present paper, we complete the analysis using an improved algorithm and an extended data base of families, and we discuss the potential errors arising from uncertainties and from the dispersion of the astronomical data. We confirm that the analysis connected to the search for the YORP-eye can lead to an estimate of the age, which is similar and strongly correlated to that obtained by the analysis of the V-slope size-dependent spreading due to the Yarkovsky effect. In principle, the YORP-eye analysis alone can lead to an estimate of the ages of other families, which have no independent age estimates. However, these estimates are usually affected by large uncertainties and, often, are not unique. Thus, they require a case-by-case analysis to be accepted, even as a rough first estimate.